Penggunaan Media “Alga Maji” Untuk Meningkatkan Hasil Belajar PAI Materi Haji Dan Umrah Kelas IX A SMP Negeri 4 Gantung - Heriyanto Heriyanto (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2020)
The aim of this learning innovation is to realize 21st century learning and the era of the industrial revolution 4.0 namely critical thinking, collaborating, communicating effectively, and creativity in learning and shaping the character of learners, as well as increasing understanding and learning outcomes in Hajj and Umrah material for class IX A SMP Negeri 4 Gantung, East Belitung Regency, Bangka Belitung Islands. Based on the results of a questionnaire from students and direct observation conducted by the teacher, as well as the results of evaluations that have been carried out, the use of the media